Melatonin Pre-harvest Treatments Leads to Maintenance of Sweet Cherry Quality During Storage by Increasing Antioxidant Systems - Carrión-Antolí, Alberto; Martínez-Romero, Domingo; Guillén, Fabián; Zapata, Pedro J.; Serrano, María; Valero, Daniel (Frontiers in Plant Science, 2022)
Melatonin has been reported to have an important role in fruit ripening, although the effect of preharvest melatonin treatment on sweet cherry quality properties during storage is still unknown. In the present experiments, the effects of melatonin (0.1, 0.3 and 0.5 Mm) by foliar spray treatments of ‘Prime Giant’ and ‘Sweet Heart’ sweet cherry trees on fruit quality traits and antioxidants systems during storage was evaluated. Results showed that these treatments reduced weight losses during storage, as well as losses in firmness and titratable acidity. In addition, changes in fruit colour and total soluble solid content were also delayed in fruit from melatonin treated trees with respect to controls. Moreover, in general, total phenolic and anthocyanin concentrations were higher in fruit from treated trees than in those from control ones, either at harvest or during the whole storage period. Finally, the activity of the antioxidant enzymes catalase, ascorbate peroxidase and peroxidase was also enhanced as a consequence of melatonin treatment. Overall results show that preharvest melatonin treatment delayed the postharvest ripening process of sweet cherry fruit, leading to maintenance of their quality properties in optimum levels for consumption two weeks more with respect to fruit from control trees. Antioxidant systems, both enzymatic and non-enzymatic ones, were also enhanced by melatonin treatments, which would account for the delay on fruit postharvest ripening process and fruit quality maintenance during storage.